Multi task hyperreconfigurable architectures: models and reconfiguration problems. (6th June 2006) - Lange, Sebastian; Middendorf, Martin
Hyperreconfigurable architectures can adapt their reconfiguration abilities during run time and have been proposed to increase the speed of dynamic reconfiguration. In this paper we study the concept of partial hyperreconfiguration for multitask environments. Several models for partially hyperreconfigurable architectures are proposed and the problem to find optimal (hyper) reconfigurations is studied. While under a general cost model the problem is known to be NP-complete even for a single task, an interesting special case is identified that can be solved in polynomial time for multiple tasks. An example for a partially hyperreconfigurable architecture is given and results of simulations with a test application are presented.